No impact of direct implantation of a self-expanding valve on one-year clinical outcomes. Insights from the multicenter, randomized DIRECT trial. (25th November 2020) - Toutouzas, K; Benetos, G; Drakopoulou, M; Karmpalioti, M; Xanthopoulou, M; Stathogiannis, K; Latsios, G; Synetos, A; Voudris, V; Kosmas, E; Mastrokostopoulos, A; Katsimagklis, G; et al.
Abstract: Introduction: The DIRECT trial (Predilatation in Transcatheter Aortic Valve Implantation Trial) evaluated in a randomized fashion the safety and efficacy of direct (without balloon pre-dilatation) implantation of a self-expanding valve in all comers undergoing TAVI. Purpose: To investigate the impact of direct implantation of a self-expanding valve on one-year clinical outcomes. Methods: DIRECT trial randomized consecutive patients with severe aortic stenosis at 4 tertiary centers to undergo TAVI with the use of self-expanding prostheses with (pre-BAV) or without pre-dilatation (no-BAV). The primary endpoint was device success according to the VARC-2 criteria. Secondary endpoints included periprocedural mortality and stroke, new permanent pacemaker implantation and vascular complications. All cause death, cardiac death, stroke and heart failure hospitalizations were recorded at one year and compared between the two groups using Kaplan-Meier plots. Results: In total 171 patients were randomized in 4 centers. In the intention to treat analysis 86 patients were randomized to the pre-BAV group and 85 patients to the no-BAV TAVI group. The device success according to the VARC-2 criteria was non-inferior in the no-BAV group compared to the pre-BAV group (65/85 - 76.5% for no-BAV versus 64/86 – 74.4% for pre-BAV, mean difference = 2.1%, 90% CI: −8.9 to 13). In the no-BAV group 25 (29.4%) patients underwent post balloon dilatation and in the pre-BAV group 13 patients (15.1%) (p=0.03). At one year 4 deaths were recorded in pre-BAV group (4.7%) and 3 deaths in no-BAV group (3.5%). There was no difference in Kaplan-Meier plots between the two groups in all-cause mortality (log-rank p=0.72, figure). Similarly, there was no difference in one-year incidence of stroke (1 in pre-BAV and 2 in no-BAV group, log-rank p=0.55), cardiac death (log-rank p=0.66), non-cardiac death (log-rank p=0.98) and heart failure hospitalizations (1 in pre-BAV versus 3 in no-BAV group, log-rank p=0.31). Lastly, there was no difference in the incidence of permanent pacemaker implantation between the two groups at one year (27/67 in no-BAV group versus 20/69 in pre-BAV group, log-rank p=0.24) Conclusions: Direct transcatheter aortic valve implantation is non-inferior to the procedure with pre-dilatation in self-expanding valve. Despite the overall low rate of events, direct procedure has no impact on clinical outcomes at one year. Funding Acknowledgement: Type of funding source: Private company. Main funding source(s): Medtronic